2005
DOI: 10.1186/1475-2891-4-35
|View full text |Cite
|
Sign up to set email alerts
|

Copper Chaperone for Cu/Zn Superoxide Dismutase is a sensitive biomarker of mild copper deficiency induced by moderately high intakes of zinc

Abstract: Background: Small increases in zinc (Zn) consumption above recommended amounts have been shown to reduce copper (Cu) status in experimental animals and humans. Recently, we have reported that copper chaperone for Cu/Zn superoxide dismutase (CCS) protein level is increased in tissues of overtly Cu-deficient rats and proposed CCS as a novel biomarker of Cu status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
0
26
1
Order By: Relevance
“…APLP2 is another protein containing a copper-binding domain that, along with the closely related APP, has been related to the regulation of copper levels in neurons [18], effect that appears to be dependent on APLP2 and APP expression [19]. On the other hand, recent reports show that CCS [20][21][22] responds to copper deficiency in rats and mice [23][24][25][26] and data from our laboratory showed that CCS also responds in a consistent way to copper excess (to be submitted) in healthy adult humans receiving 8 mg Cu/day for 6 months.…”
Section: Introductionmentioning
confidence: 97%
“…APLP2 is another protein containing a copper-binding domain that, along with the closely related APP, has been related to the regulation of copper levels in neurons [18], effect that appears to be dependent on APLP2 and APP expression [19]. On the other hand, recent reports show that CCS [20][21][22] responds to copper deficiency in rats and mice [23][24][25][26] and data from our laboratory showed that CCS also responds in a consistent way to copper excess (to be submitted) in healthy adult humans receiving 8 mg Cu/day for 6 months.…”
Section: Introductionmentioning
confidence: 97%
“…A recent field study confirms that direct analysis of copper in the liver is the best biomarker of supraoptimal copper exposure (López-Alonso et al, 2006). Copper chaperone for copper/zinc superoxide dismutase is a sensitive biomarker for copper deficiency (Iskandar et al, 2005;Denzeisen et al, 2007).…”
Section: Efficacymentioning
confidence: 86%
“…Ctr1 knockout mice die in utero in midgestation, establishing a critical role for Ctr1 in embryonic development (Lee et al 2001;Kuo et al 2001). Ctr1 +/− mice and intestinal epithelial cellspecific Ctr1 knockout mice show reduced Cu accumulation in peripheral tissues and other phenotypes indicative of Cu deficiency underscoring an essential role for Ctr1 in Cu uptake at the intestinal level and in peripheral tissues (Lee et al 2001;Nose et al 2006;Kuo et al 2001).…”
Section: Cu Trafficking By Ctr2mentioning
confidence: 93%
“…All initial studies demonstrating upregulation of CCS used tissues from overtly Cudeficient rats or mice. To test whether CCS could detect small reductions in Cu status, we induced mild Cu deficiency in rats by feeding diets moderately high in Zn (Iskandar et al 2005). CCS protein was increased in liver, erythrocytes, and white blood cells of rats fed elevated levels of Zn.…”
Section: Ccs As a Biomarker Of Cu Statusmentioning
confidence: 99%
See 1 more Smart Citation